(untitled) (GIST – Education and Learning Research Journal, 2021)
This case study attempts to elucidate the effects that the use of mobile phones as tools for teaching reading have in fostering motivation in EFL students. Through the use of qualitative research techniques, the professor executes a set of activities in a reading techniques course for second-year English language learners; focus groups and questionnaires help gather the students’ perceptions on their involvement, enjoyment, and investment; the atmosphere created during the implementation of the activities, and their overall experience. In conclusion, the ubiquity of cell phones provides advantages in the development of motivation towards learning English and in fostering independence.